Metamorphosis of Nepal-China Relations - Bhatta, Chandra Dev (NCWA Annual Journal, 2024)
This article explains how Nepal-China relations would unfold at a time when China is on the verge of becoming a superpower while Nepal is sadly still reeling under political instability and economic underdevelopment and is largely unable to address new geopolitical challenges. How geopolitics pans out in South Asia in general and the Himalayan region, in particular, will determine Nepal’s relations with China in the days to come. Nepal-China relations are historical, but they are only such in the sense that both states have existed since time immemorial and lived side by side. Yet understanding the nature of relations between the two neighbors has been difficult. Many would not like it but the fact remains that we do not see much of historical intricacies of significance between the two countries. How things are evolving in the recent past and present would shape the relations in the future. At the bilateral level, China prefers that (a) Nepal recognizes Tibet as an integral part of China (b) Nepal embraces the One-China policy (now moved towards the One-China principle) concerning Taiwan, and (c) Nepal does not allow its territory to be used against China by others. Nepal, however, does not seek/demand any such commitment from China. Does China reciprocate in the same manner and method? How does China prioritize Nepal with regard to its foreign policy? These are some of the key questions requiring careful answers. Certainly, this paper cannot delve into all of them but will only give a perspective in that regard.